A method of determining the parameters in systems with serialized Current-Voltage characteristics - Ocaya, R.O.; Yakuphanoğlu, Fahrettin (IOP Publishing Ltd, 2021)
We propose a method of determining the parameters of systems with serialized characteristics, which may suggest the existence of symmetry in the system. The method is demonstrated in extracting the parameters of a metal-semiconductor in the presence of significant series resistance, which is itself important but limits the accuracy of the existing methods in the determination of the other calculated parameters such as barrier height and ideality factor. We show the steps involved in establishing whether symmetry exists, and show that some functional interrelations between the parameters and the independent variables can readily be established. We use actual measurement data from an experimental diode and show that the results outperform the popular Cheung-Cheung approach. This general approach, therefore, represents a significant advancement in the analysis of serialized empirical data. © 2021 Institute of Physics Publishing. All rights reserved.
10th International Conference on Mathematical Modeling in Physical Sciences, IC-MSQUARE 2021 -- 6 September 2021 through 9 September 2021 -- Virtual, Online -- 175460
Keywords: Electric resistance; Actual measurements; Barrier heights; Current-voltage characteristics; Empirical data; Ideality factors; Independent variables; Measurement data; Metal semiconductors; Series resistances; Current voltage characteristics